If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(3a + -3) = 3(a + -1) Reorder the terms: -7(-3 + 3a) = 3(a + -1) (-3 * -7 + 3a * -7) = 3(a + -1) (21 + -21a) = 3(a + -1) Reorder the terms: 21 + -21a = 3(-1 + a) 21 + -21a = (-1 * 3 + a * 3) 21 + -21a = (-3 + 3a) Solving 21 + -21a = -3 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 21 + -21a + -3a = -3 + 3a + -3a Combine like terms: -21a + -3a = -24a 21 + -24a = -3 + 3a + -3a Combine like terms: 3a + -3a = 0 21 + -24a = -3 + 0 21 + -24a = -3 Add '-21' to each side of the equation. 21 + -21 + -24a = -3 + -21 Combine like terms: 21 + -21 = 0 0 + -24a = -3 + -21 -24a = -3 + -21 Combine like terms: -3 + -21 = -24 -24a = -24 Divide each side by '-24'. a = 1 Simplifying a = 1
| x^3+8x^2+10x=2x^2+5x | | 14b^2+a-2b^2=0 | | 2x+(2x-5)=145 | | 0=-2y+3+10 | | (6y+9)2/3=10 | | u(v+3)+w(u-8)=z(v-1) | | 0=-2y+2+10 | | 11*6x-5*30x=868 | | 8x+30=0 | | 33/5+1/2n=119/40 | | 3x+13+5x-7=180 | | 34=5b-3(8-8b) | | 0=-2y+1+10 | | 5(3x-6)=25 | | 5(3x-6)=25 | | -8(r+11)=16-8r | | 3x+13+5x-7=90 | | 14b^2-2b^2=0 | | 8+5*2/12 | | 0=-2y+0+10 | | 14b-12(11-2b)=20 | | 0=-2y+x+10 | | A/-9=11 | | -4=3x-14/2 | | -4=2x+2+4x | | .4(x+2)-.7(x+2)=.3x-.6 | | 4-7(k+5)=-8(4+k)-8 | | -1.3m=-6.5 | | i=pxt | | 36=-6(1-7v) | | 7(5x-4)=20 | | 24+3^3/(-27)*9 |